Heteroaryl-Fused Triazapentalenes: Synthesis and Aggregation-Induced Emission - Yingchun Wang; Thanh Chung Pham; Jianjun Huang; Junfeng Wu; Wim Dehaen (Molecules)
A pyridine-fused triazapentalene shows weak fluorescence in solution and is readily accessible via nitrene-mediated cyclization. In this study, a modified Cadogan reaction was used to synthesize HetATAP 1. Palladium-catalyzed reactions have been used as post-functionalization methods. Interestingly, modified Suzuki cross-couplings with various boronic acids resulted in poor to moderate yields of HetATAPs 2–5 which were arylated at the azole moiety. Direct CH arylation of HetATAP 1 gave the products with the same regiochemistry in satisfactory yields. The structures of HetATAPs 2–5 were confirmed using NMR analysis. In addition, the photophysical properties of HetATAPs 1–5 were studied under various conditions. Particularly, the emission of HetATAPs 2–5 is enhanced in the solid and aggregate state.